Immune Landscape of the Tumor Microenvironment Identifies Prognostic Gene Signature CD4/CD68/CSF1R in Osteosarcoma - Song, Yi-jiang; Xu, Yanyang; Zhu, Xiaojun; Fu, Jianchang; Deng, Chuangzhong; Chen, Hongmin; Xu, Huaiyuan; Song, Guohui; Lu, Jinchang; Tang, Qinglian; Wang, Jin (Frontiers in Oncology, 2020)
Background: Osteosarcoma (OSA), the most common primary bone malignancy in children and adolescents, is prone to metastases and unfavorable prognosis. Owing to its strong genomic heterogeneity, traditional chemotherapy, or targeted immunotherapy has not effectively improved the related overall survival for decades. Since the landscape of the OSA tumor immune microenvironment is scarcely known, despite it playing a crucial role in predicting clinical outcomes and therapeutic efficacies, we aimed to elucidate its molecular characteristics. Methods: The immune signature of 101 OSA samples was explored using transcriptome profiling and clinical characteristics retrieved from the Therapeutically Applicable Research to Generate Effective Treatments (TARGET) program. Correlations between the prognostic immune markers and their clinical chemotherapy responses were assessed and verified based on 45 OSA primary tumors. Findings: We identified the heterogeneity underlying tumor immune signature in OSA, and found CD4+ T cells and macrophage markers CD4/IFNGR2/CD68 to be feasible prognostic factors, exerting significantly positive correlation with each other. Specifically, CSF1R, which plays an essential role in the regulation of proliferation and differentiation of macrophages, was found to be a specific signature associated with CD4/CD68, with improved OSA clinical outcomes. Interpretation: The immune landscape based on CD4/CD68/CSF1R gene signatures showed considerable promise for prognostic and therapeutic stratification in OSA patients. A specific immune signature for OSA, abundantly consisting of Th1-polarized CD4+ T cells and CSF1R-related CD68+ macrophages, may improve the predictive efficacy of chemotherapy and improve prognosis in patients with OSA.